Penggunaan Website Wordwall Sebagai Media Pembelajaran Untuk Meningkatkan Motivasi Belajar Siswa di SMK Bima Utomo - Tigor Sitohang; Eva Dita Yanti Simanjuntak; Sarah Evelyn Samosir; Mindela Frida Panggabean; Sarah Evelyn Simanjuntak (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
A teaching program is a plan for implementing the teaching and learning process which is based on consideration of the objectives to be achieved, materials, methods, tools, time allocation and evaluation so that students master the learning process and have optimal learning outcomes. Wordwall is an interactive media that provides features to foster student learning motivation according to the learning material presented by the teacher in class. Word wall media provides features such as quizzes, matching, pairing, anagrams, random words, word searches, grouping. The PkM (Community Service) Lecture Program with the title "Using the Wordwall Website as a Learning Media to Increase Student Learning Motivation at Bima Utomo BS Vocational School" is carried out by prioritizing how to use the wordwall website, especially for teachers or teaching staff at Bima Utomo BS Vocational School with the main aim increase student learning motivation and make it easier for teachers to deliver learning material. The results of the implementation of Community Service at BIMA UTOMO BS Vocational School, Sidodadi Village, Batang Kuis District, Deli Serdang Regency, North Sumatra which was carried out from February 5 - February 27 2024, the team was able to adapt well so that a cooperative relationship was established between the school, students and students, teachers are able to use wordwall media as an interactive learning media for the continuity of teaching and learning activities, socialize the use of wordwall media as an interactive learning media, provide contributions in the form of assistance to the school regarding administration and students feel motivated by the existence of interactive learning media.